Origin of a Jury Trial in the European Countries - Hamitov, Radik N.; Tumanov, Dmitriy Yu.; Sakhapov, Rinat R. (Journal of History Culture and Art Research, 2017)
Traditionally it is believed that the birthplace of the jury trial creation is England, but the issue of the birthplace location of this particular form of popular participation in the criminal justice administration is not yet fully resolved by the historical science. The continental lawyers were particularly interested in the jury trial among other institutions of English law, in which the English themselves identified the stronghold of the country's law and order, its political and civil freedom. It is not difficult to see that the main role was not played by the judges, but by the community representatives in this form of justice administration. Since then the community has been gaining more and more importance in England as a state body in the matter of justice administration, and the initial forms of its activity have being further developed in this direction. This works investigates roots of jury trial by basing on such methods as historical, systemic, formally logical, concrete-historical, comparative legal analysis method. The authors, in turn, come to the conclusion that the jury trial has its roots still in the Ancient States, but the classical modern model owes its origin to England.